Dampak Teknologi Informasi terhadap Pola Interaksi Masyarakat : Studi Kasus di Desa Jantuk Lombok Timur - Madani Putri; Lalu Sumardi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to find out and explain the impact of information technology on the interaction patterns of the Jantuk community. Case study in East Lombok. The approach used is through a qualitative study with a case study type of research. Sources of data in this study were obtained from informants, namely the public, sources of relevant journal books that had previously existed articles and previous research. Data collection techniques were obtained by means of interviews and observations. Comparing with data in similar journals. Data analysis techniques in this study used interactive model analysis developed by Miles, Huberman and Saldana with three techniques namely: data reduction, data display and drawing conclusions. The results of the study show that the impact of information technology, especially gadgets, can change the interaction pattern of the Jantuk village community, the Jantuk village community initially did a lot of direct interaction but now interaction can be done through gadgets. However, the impact of information technology, like gadgets, has positive and negative impacts, depending on the usage of each person. It is undeniable that gadgets can change patterns of interaction in society.